1981
DOI: 10.1111/j.1440-1681.1981.tb00753.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of Angiotensin Converting Enzyme by Cultured Bovine Endothelial Cells

Abstract: 1. Endothelial cells from bovine aortae were grown to confluence in tissue culture. The cells were subcultured and angiotensin converting enzyme (ACE) production was measured while the cells were maintained in serum-free medium for 4 days. 2. During this period, there was a ten-fold increase in ACE concentration in the medium whereas the cellular content of the enzyme remained constant at approximately 23% of the total enzyme produced. Cycloheximide (1 mumol/l) blocked production of ACE. 3. The enzyme liberate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Alhenc-Galas (1982) also showed that captopril was without effect on prostacyclin production induced by Bk in human cultured endothelial cells. Endothelial cells produce ACE in vitro (Mendelsohn & Kachel, 1981), so that a potentiation of the effect of Bk by captopril might be expected, as seen in the guinea-pig isolated lungs. However, there are many more endothelial cells in a guinea-pig isolated lung (109) than in our column of endothelial cells (107).…”
Section: Discussionmentioning
confidence: 98%
“…Alhenc-Galas (1982) also showed that captopril was without effect on prostacyclin production induced by Bk in human cultured endothelial cells. Endothelial cells produce ACE in vitro (Mendelsohn & Kachel, 1981), so that a potentiation of the effect of Bk by captopril might be expected, as seen in the guinea-pig isolated lungs. However, there are many more endothelial cells in a guinea-pig isolated lung (109) than in our column of endothelial cells (107).…”
Section: Discussionmentioning
confidence: 98%
“…Techniques for harvesting and culture of endothelial cells have been described (6), and the cultured cells have been shown to produce ACE in vitro (7). We therefore chose cultured endothelial cells as a convenient system to investigate the regulation of ACE production.…”
Section: Introductionmentioning
confidence: 99%